Dukungan Laki-Laki terhadap Kepemimpinan Perempuan dalam Organisasi Mahasiswa: Studi Unit Kegiatan Mahasiswa Universitas Andalas - Andru Zulya Saputra (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2019)
The purpose of this study is to explain support of men to women leadership in student organizations, explaining reasons of men to support women leadership and differences ofmen’s reasons to support and do not support women leadership. In this study structuration theoryof Anthony Giddens was used, the qualitative research method is also used. From the results of this study, it can be concluded that mean’s trust in female leadership is law, but men do support elected female leaders in carrying out their duties as leaders. The forms of male support for women leadership are professionalsupport: giving direct input and helping off-campus activities or strenuous activities